Blessings in Trade According to The Views of Banjar Traders in Palangka Raya City with An Anthropological and Religious Approaches - Kurniawan, Rahmad; Rofiq , Aunur; Khusnudin (Iqtishodia: Jurnal Ekonomi Syariah, 2024)
Islam requires every mature individual to seek legal livelihood, one of which is through trade. However, some traders sometimes do not pay attention to the provisions of Islamic commercial transactions (muamalah). In this regard, there is an interesting phenomenon among some Banjar traders at the Pasar Besar in Palangka Raya. They emphasize more on the concept of "blessing" (barakah), so that trading (business) activities and worship are in balance. Each person and region understand "blessing" differently, both in terms of its meaning, causes, and benchmarks. This research examines the meaning of "blessing" according to the traders, as well as analyzing the anthropological aspects related to the trading practices oriented towards "blessing". This is a qualitative descriptive study with Banjar traders at the Pasar Besar in Palangka Raya as the research subjects. The findings show that the meaning of "blessing" in trading according to Banjar traders is the increase in goodness, abundance or increase in sustenance, beneficial for all, so that needs are met. "Blessing" is also interpreted as the achievement of pleasure, tranquility, peace, and comfort in life. The position of "blessing" in trading is very important, because the purpose of trading is to fulfill life's needs in accordance with Islamic sharia. Blessing will not be obtained if the provisions of Islamic business are ignored. Anthropologically, trading practices oriented towards "blessing" indicate a close relationship between economic activity and the belief system and religious values embraced by the Banjar trader community